#TITLE_ALTERNATIVE# - (NIM 20297017); Pembimbing: Gunawan Handayani, MSCE, Ph.D., ERFAN
We have measured the velocities and attenuation of compressional and shear waves of loose sand sample with relative density ranges from 0 to 100%. The measurements were made using the sonic viewer equipment. An analog to digital card model PCL-1800 collects the data. The results show that for this sample, compressional and shear wave velocities increase with increasing relative densities but attenuation decreases with the increase of relative density. To develop methods for evaluation of liquefaction potential in the field using seismic waves propagation theory , the correlations were made among wave propagation properties, i.e. velocity and attenuation, and ground maximum acceleration due to earthquakes. The results of correlation show that the soil deposit with high velocity waves tends to not liquefy but the soil deposit with high attenuation tends to liquefy.